Carnosol suppresses RANKL‐induced osteoclastogenesis and attenuates titanium particles‐induced osteolysis. Issue 3 (28th July 2020) - Li, Yongxian; Lin, Sipeng; Liu, Panjie; Huang, Jianbin; Qiu, Junxiong; Wen, Zhenkang; Yuan, Jinbo; Qiu, Heng; Liu, Yuhao; Liu, Qian; Zhou, Tengpeng; Luo, Peijie; et al.
Abstract: Osteolysis is a common medical condition characterized by excessive activity of osteoclasts and bone resorption, leading to severe poor quality of life. It is essential to identify the medications that can effectively suppress the excessive differentiation and function of osteoclasts to prevent and reduce the osteolytic conditions. It has been reported that Carnosol (Car), isolated from rosemary and salvia, has anti‐inflammatory, antioxidative, and anticancer effects, but its activity on osteolysis has not been determined. In this study, we found that Car has a strong inhibitory effect on the receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclast differentiation dose‐dependently without any observable cytotoxicity. Moreover, Car can inhibit the RANKL‐induced osteoclastogenesis and resorptive function via suppressing NFATc1, which is a result of affecting MAPK, NF‐κB and Ca 2+ signaling pathways. Moreover, the particle‐induced osteolysis mouse model confirmed that Car could be effective for the treatment of bone loss in vivo. Taken together, by suppressing the formation and function of RANKL‐induced osteoclast, Car, may be a therapeutic supplementary in the prevention or the treatment of osteolysis. Abstract : Osteolysis is a common medical condition characterized by excessive activity of osteoclasts and bone resorption, leading to severe poor quality of life. It is essential to identify the medications that can effectively suppress the excessive differentiation and function of osteoclasts to prevent and reduce the osteolytic conditions. It has been reported that Carnosol (Car), isolated from rosemary and salvia, has anti‐inflammatory, antioxidative, and anticancer effects, but its activity on osteolysis has not been determined. In this study, we found that Car has a strong inhibitory effect on the RANKL‐induced osteoclast differentiation dose‐dependently without any observable cytotoxicity. Moreover, Car can inhibit the RANKL‐induced osteoclastogenesis and resorptive function via suppressing NFATc1, which is a result of affecting MAPK, NF‐κB, and Ca 2+ signaling pathways. Moreover, the particle‐induced osteolysis mouse model confirmed that Car could be effective for the treatment of bone loss in vivo. Taken together, by suppressing the formation and function of RANKL‐induced osteoclast, Car, may be a therapeutic supplementary in the prevention or the treatment of osteolysis.